Social enterprise and wellbeing in community life. Issue 2 (1st August 2016) - Farmer, Jane; De Cotta, Tracy; McKinnon, Katharine; Barraket, Jo; Munoz, Sarah-Anne; Douglas, Heather; Roy, Michael James
Abstract : Purpose: This paper explores the wellbeing impacts of social enterprise, beyond a social enterprise per se, in everyday community life. Design/methodology/approach: An exploratory case study was used. The study's underpinning theory is from relational geography, including Spaces of Wellbeing Theory and therapeutic assemblage. These theories underpin data collection methods. Nine social enterprise participants were engaged in mental mapping and walking interviews. Four other informants with 'boundary-spanning' roles involving knowledge of the social enterprise and the community, were interviewed. Data were managed using NVivo, and analysed thematically. Findings: Wellbeing realised from 'being inside' a social enterprise organisation was further developed for participants, in the community, through positive interactions with people, material objects, stories and performances of wellbeing that occurred in everyday community life. Boundary spanning community members had roles in referring participants to social enterprise, mediating between participants and structures of community life, and in normalising social enterprise in the community. They also gained benefit from social enterprise involvement. Originality/value: This paper uses relational geography and aligned methods to reveal the intricate connections between social enterprise and wellbeing realisation in community life. There is potential to pursue this research on a larger scale to provide needed evidence about how wellbeing is realised in social enterprises and then extends into communities.